Fundamentals of reliability engineering : applications in multistage interconnection networks - Gunawan, Indra (Hoboken, N.J. : Scrivener Publishing/John Wiley & Sons, Inc., 2014)
This book presents fundamentals of reliability engineering with its applications in evaluating reliability of multistage interconnection networks. In the first part of the book, it introduces the concept of reliability engineering, elements of probability theory, probability distributions, availability and data analysis. The second part of the book provides an overview of parallel/distributed computing, network design considerations, and more. The book covers a comprehensive reliability engineering methods and its practical aspects in the interconnection network systems. Students, enginee.
9.1 Reliability Analysis of Shuffle-Exchange Network with Minimal Extra Stages 9.1.1 Terminal Reliability Comparison of SEN, SEN+, and SEN+2; 9.1.2 Broadcast Reliability Comparison of SEN, SEN+, and SEN+2; 9.1.3 Network Reliability Comparison of SEN, SEN+, and SEN+2; 9.1.4 Concluding Remarks; 9.2 Terminal Reliability Improvement in Modified Shuffle-Exchange Network; 9.2.1 Terminal Reliability of Shuffle-Exchange Network (SEN); 9.2.2 Terminal Reliability of Modified Shuffle-Exchange Network (MODSEN); 9.2.3 Comparison of the Networks; 9.2.4 Conclusion; 9.3 Reliability Bounds for Large MINs.
Includes bibliographical references and index.
Description based on print version record and CIP data provided by publisher.
Keywords: Interconnects (Integrated circuit technology); Reliability (Engineering); Communication -- Network analysis; Computer networks; Telecommunication -- Switching systems; TECHNOLOGY & ENGINEERING -- Engineering (General); TECHNOLOGY & ENGINEERING -- Reference; Interconnects (Integrated circuit technology); Reliability (Engineering); Electronic books; Electronic books